Focused ion beam nanomachining and nanopatterning for optical structure fabrication - Wang, Houxiao (2013)
With the development of the nano-precision facilities and technologies, more interest has been gained to develop functional bio-inspired materials and devices as well as the plasmonic devices due to their promising potential for various applications, among which the nanoscale optical structures have gained much more attention for the applications in the fields of photonics, electronics, sensing, biology, and solar cells, etc. An important technical focus on these areas is the selection of appropriate mirco- or nano-scale tools and techniques for various applications. Focused ion beam (FIB) has its strength in one-step maskless simpler, more flexible, and better-controlled nano-precision machining, patterning and fabrication especially for submicron or nanoscale various functional samples or structures. Besides, another advantage of FIB is that it can be conveniently used to machine the biology to analyze its structures, and FIB nanopatterning can be further used to fabricate the designed nanostructures inspired by the observed biostructures. Moreover, another important interest regarding the development of plasmonic structures is how to make them precisely designed and fabricated using the existing simulation and nanofabrication techniques and facilities. Accordingly, this investigation primarily aims to develop various functional bio-inspired and plasmonic optical structures mainly using FIB and finite difference time domain (FDTD) computation method based on the structural analyses for human hairs and butterfly wings to decipher their structural colors as well as the FIB-assisted interface endpoint detection.